What colour is penguin guano?. Issue 5 (23rd June 2017) - Rees, W.G.; Brown, J.A.; Fretwell, P.T.; Trathan, P.N.
Abstract: The identification and quantification of Antarctic Pygoscelis penguin colonies depends increasingly on recognition of the characteristic optical properties of guano deposits, but almost all knowledge of these properties until now has been compromised by resolution and atmospheric propagation effects. Here we present hyperspectral reflectance data in the range 350–2500 nm, collected in situ from fresh guano deposits in Pygoscelis penguin colonies on Signy Island, South Orkney Islands. The period of data collection included the transition from predominantly white guano to the pink coloration characteristic of a krill-rich diet. The main identifiable features in the spectra are a broad absorption feature centred around 550 nm, responsible for the pink coloration and identified with the pigment astaxanthin, as well as several water absorption features. Variations in these features are responsible for differentiation between spectra. From these results we propose two spectral indices suitable for use with satellite data, one of which responds to the presence of astaxanthin in the guano and the other to water. Our results do not allow us to differentiate between penguin species from their guano, but do suggest that the breeding phenology of Pygoscelis penguins could be determined from a time series of multispectral imagery.